Career Development Service Model in Higher Education: A Comparative Study of Career Center Services at State-Owned Universities (PTN) and Islamic Higher Education Institutions (PTKIN) - Nur Fitriyani Hardi; Noor Saif Muhammad Mussafi; Siti Rohaya; Citra Widyastuti (Yayasan Darussalam Bengkulu, 2026)
Career Development Services in Higher Education are a crucial pillar in producing productive, work-ready graduates. In practice, each university faces various obstacles in preparing students for their careers, both in terms of infrastructure and external networks. This study aims to compare career development service models at State Universities (PTN) and State Islamic Religious Universities (PTKIN), focusing on the career centers of the Sepuluh Nopember Institute of Technology (ITS) and UIN Sunan Kalijaga Yogyakarta. This research uses a qualitative descriptive approach, with data collected through semi-structured interviews and Focus Group Discussions (FGDs) involving career center administrators. The results show that both institutions provide similar core services, including career counseling, job vacancy information, recruitment programs, job fairs, and tracer studies. These services are designed to bridge the gap between graduates and the labor market while enhancing students’ competencies and employability. However, differences are found in institutional structure, service delivery, and program emphasis. ITS demonstrates a stronger system in managing career portals and establishing partnerships with industry, which facilitates alumni connections with companies. In contrast, UIN Sunan Kalijaga shows greater emphasis on career preparation through structured graduation briefing programs and continuous career guidance. In conclusion, although PTN and PTKIN share similar objectives in supporting student career development, their service models differ in implementation strategies and institutional priorities. These findings highlight the importance of strengthening career center services to improve graduate readiness and competitiveness in the labor market.